PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. CHRISTALENTA PRATAMA - Willy Jermias Abdi; Rasmansyah (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This study aims to determine: (1) the effect of competence on the performance of employees of PT. Christalenta Pratama, (2) the effect of work discipline on the performance of the employees of PT. Christalenta Pratama, and (3) simultaneous influence of competence and work discipline on the performance of the employees of PT. Christalenta Pratama. This research is causal associative research with quantitative approach. The population of this study is all employees of PT. Christalenta Pratama, amounting to 60 people. Data is collected by a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that: (1) there was a positive and significant effect of competence on the performance of the employees of PT. Christalenta Pratama; (2) there is a positive and significant influence of work discipline on the performance of employees of PT. Christalenta Pratama, and (3) there is a simultaneous influence of competence and work discipline on the performance of the employees of PT. Christalenta Pratama